Σύλληψη αλλοδαπού για παράβαση του νόμου περί εξαρτησιογόνων ουσιών στη Χίο (HellenicCoastguard, 2020)
: ΓΙΟΤΑΚΙΑΣΕΣΑΝΕΣΟΝΟΣΕΣΗΣΑΝΟΣΕΣΗΣΕΣΗΣΑΝΕΣΙΣΑΝΕΣΗΣΩΣΗΣΗΣΕΣΑΝΕΣΕΣΗΣΗΣΑΝΕΣΗΣΑΝΕΣΕΣΗΣΕΣΑΝΕΣΗΣΕΣΗΣΕΣΗΣΕΣΗΣΗΣΕΣΗΣΗΣΗΣΗΣΗ